Fabrication of MSM UV photodetector based on ZnO films synthesized by RF magnetron sputtering / Halim Ahmad, Mat Johar Abdullah and Ajis Lepit - Ahmad, Halim; Abdullah, Mat Johar; Lepit, Ajis (Universiti Teknologi MARA, Sabah, 2017)
C-axis oriented ZnO films were deposited on SiO2/Si substrates through RF magnetron sputtering, MSM UV photodetector using Ag/ZnO/Ag configuration were fabricated from the as prepared film while the heat treated film was used to fabricate MSM Schottky barrier UV photodetector using Al/ZnO/Ag configuration. The crystalline and optical quality of the film had improved after the heat treatment. It was found that the Schottky barrier heights as prepared and heat treated using Ag/ZnO interface was around 0.74 and 0.76 eV respectively. The leakage current was reduced from 18.6 mA to 0.6 μA at 5V after post deposition annealing when compared with that of as deposited ZnO.The Ag/ZnO/Ag configuration showed a faster decay time of 212 s.